The Correlation of Vocabulary Mastery, Reading Interest, and Writing Expositions Text in Senior High Class Students - Susana, Hera; Istiara, Febriyantina; Maryova, Frieska; Dwi Ajeng, Galuh (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2021)
The purpose of this study is to analyze the problems in this study is the correlation of vocabulary mastery and reading interest with the ability to make up exposition in students of class X SMAN I Banjar Margo Tulang Bawang This research was carried out due to the fact in the field that the ability to make up exposition and mastery of reading interests, as well as vocabulary mastery that needs to be feared. This study aims to describe the correlation between vocabulary mastery and mastery of reading interest with the ability to make up expositions of students of class X SMAN I Banjar Margo Tulang Bawang. The author uses a correlational method, meaning that the data is collected after all the events in direct question. The technique used in retrieving research data is a test. Research data analysis techniques include analysis requirements tests, statisti analysis, and research hypothesis testing techniques. The results of research on this thesis concluded 1) there is a positive and significant correlation between vocabulary mastery and exposition writing ability, indicated by the correlation coefficient of 0.772 and the coefficient of determination (r2) of 0.596 or 0.772 and the coefficient of determination (r2) of .596 or 59.69%, 2) there is a positive and significant correlation between mastery of reading interest and the ability to write exposition indicated by the correlation coefficient of 0.713 and the coefficient of determination (r2) of 0.508 or by 59.80%; 3) there is a positive and significant correlation between vocabulary mastery and mastery of reading interest with the ability to write expositions indicated by a correlation coefficient of 0.810 coefficient of determination (r2) of 0.656 or 65.60%.